Group processes and interoperability: A longitudinal case study analysis of the UK's civil contingency response to Covid‐19. (7th July 2022) - Radburn, Matthew; Stott, Clifford; Bryant, Rebecca; Morgan, Bethan; Tallent, Deborah; Davidson, Louise
Abstract: Our case study explored a Local Resilience Forum's (LRF) civil contingency response to COVID‐19 in the United Kingdom. We undertook 19 semistructured ethnographic longitudinal interviews, between March 25, 2020 and February 17, 2021, with a Director of a Civil Contingencies Unit and a Chief Fire Officer who both played key roles within their LRF. Within these interviews, we focused on their strategic level decision‐making and how their relationship with national government impacted on local processes and outcomes. Using a form of grounded theory, our data describe the chronological evolution of an increasingly effective localized approach toward outbreak control and a growing resilience in dealing with concurrent emergency incidents. However, we also highlight how national government organizations imposed central control on aspects of the response in ways that undermined or misaligned with local preparedness. Thus, during emergencies, central governments can undermine the principle of subsidiarity and damage the ways in which LRFs can help scaffold local resilience. Our work contributes to the theoretical understanding of the social psychological factors that can shape the behaviour of responder agencies during a prolonged crisis. In particular, the implications of our analysis for advancing our conceptual understanding of strategic decision‐making during emergencies are discussed.